Geometry‐Assisted Three‐Dimensional Superlocalization Imaging of Single‐Molecule Catalysis on Modular Multilayer Nanocatalysts1. Issue 47 (26th September 2014) - Han, Rui; Ha, Ji Won; Xiao, Chaoxian; Pei, Yuchen; Qi, Zhiyuan; Dong, Bin; Bormann, Nicholas L.; Huang, Wenyu; Fang, Ning
Abstract To establish the structure–catalytic property relationships of heterogeneous catalysts, a detailed characterization of the three‐dimensional (3D) distribution of active sites on a single catalyst is essential. Single‐particle catalysis of a modular multilayer catalytic platform that consists of a solid silica core, a mesoporous silica shell, and uniformly distributed Pt nanoparticles sandwiched in between these layers is presented. The first 3D high‐resolution super‐localization imaging of single fluorescent molecules produced at active sites on the core‐shell model nanocatalysts is demonstrated. The 3D mapping is aided by the well‐defined geometry and a correlation study in scanning electron microscopy and total internal reflection fluorescence and scattering microscopy. This approach can be generalized to study other nano‐ and mesoscale structures.